Reducing Climate Risks by Improving Food Production and Value Chains: A Case of Sandy Soils in Semi-arid Kenya - Nkurunziza, Libère; Kuyah, Shem; Nyawira, Sylvia; Ng'ang'a, Stanley Karanja; Musei, Sylus; Chirinda, Ngonidzashe; Karugu, Winifred; Smucker, Alvin; Öborn, Ingrid (Frontiers in Climate, 2022)
Due to climate change and variability, extreme weather events are becoming more frequent worldwide, causing significant reductions in agricultural production and food security. The livelihoods of smallholder farmers, especially those eking out a living by farming on sandy soils, are particularly affected. We examined this issue using the case of Makueni County, a semi-arid area with sandy soils in south-eastern Kenya. Using survey data from 202 households, we examined extreme weather events affecting smallholder farmers and current management strategies used to mitigate the consequences. We then performed field experiments to assess potential gains of implementing sub-surface water retention technology (SWRT) in the region. Finally, we held group discussions with stakeholders in food value chains (FVC) to identify ways of managing climate risks to smallholder farmers. Analysis of the survey data showed that 199 of 202 farmers surveyed had experienced an extreme event associated with climate change and variability during the previous five years. Of these 199 farmers, 161 reported having changed their farming practices to adapt, especially to drought (70%) and increased temperature (22%). Common adaptation practices included early planting, reducing the area under cultivation, and water harvesting. In the field experiments, using SWRT resulted in a 50, 100, 150, and 170% increase in maize grain yield, cob numbers, cob weight, and maize stover biomass, respectively, compared with the control (without SWRT). Stakeholder group discussions along the FVC demonstrated a need for synergy among actors to mitigate climate risks caused by extreme weather events. These findings suggest that diversification of management strategies at farm level, combined with external inputs (new technologies, improved seeds, etc.) and services (credit access, learning from peers and professionals), will be instrumental in reducing future climate risks to smallholder farmers. Improving access to viable markets and fostering mutually beneficial linkages with post-harvest processors would add value to farm produce, thus further increasing income and the capacity of smallholder farmers to manage climate risks.